High Calcineurin Inhibitor Intrapatient Variability Is Associated With Renal Allograft Inflammation, Chronicity, and Graft Loss - Akhil Sharma, MD; Aravind Cherukuri, MD, PhD; Rajil B. Mehta, MD; Puneet Sood, MD; Sundaram Hariharan, MD (Transplantation Direct, 2019)
Background. High calcineurin inhibitor (CNI) intrapatient variability (IPV) has been associated with poor kidney allograft outcomes. However, the relationship between early allograft histological changes, their progression, and CNI-IPV is less well studied. Hence, we evaluated effect of CNI-IPV defined by the degree of fluctuation of CNI levels in all kidney transplant patients over 2 to 12 months posttransplant on early allograft inflammation, subsequent chronicity, and later clinical outcomes. Methods. Two hundred eighty-six patients transplanted from January 2013 to November 2014 were enrolled with protocol and indication biopsies. The mean CNI-IPV was 28.5% and a quarter of our cohort had IPV of 35% or greater (high CNI IPV). Baseline demographic differences were similar between high and low CNI IPV groups. Results. High CNI-IPV was associated with a higher incidence of acute rejection (AR) within 1 year (52% vs 31% P < 0.001), more persistent/recurrent AR by 1 year (18.2% vs 6.2%, P = 0.002), higher-grade AR (≥Banff 1B, 27.5% vs 7.3%, P < 0.001), and worse interstitial fibrosis/tubular atrophy (P = 0.005). High CNI-IPV was associated with increased graft loss (GL) and impending graft loss (iGL, defined as eGFR<30 ml/min and >30% decline in eGFR from baseline), regardless of donor-specific antibody, delayed graft function, rejection, or race. In a multivariate Cox Proportional Hazards Model, high CNI-IPV was independently associated with GL + iGL (hazard ratio, 3.1; 95% confidence interval, 1.6–5.9, P < 0.001). Conclusions. High CNI-IPV within 1 year posttransplant is associated with higher incidence of AR, severe AR, allograft chronicity, GL, and iGL. This represents a subset of patients who are at risk for poor kidney transplant outcomes and potentially a modifiable risk factor for late allograft loss.